Nekton - (:unkn) unknown (Dr. W. Junk b.v., The Hague, 1977)
Nekton as an ecomorphological type of biont The term nekton was suggested and used for the first time in 1890 by E. Haeckel in his book Plankton-Studien. Etymologically the word nekton derives from the Greek VTJKTTJP, i.e. swimming. As Haeckel defined it, nekton describes collectively all swimming animals that are 'free to choose their path', i.e. can resist a strong current of water and, distinct from planktonic animals, go where they wish. While giving a general idea of the dividing line between plankton and nekton, Haeckel's definition, which has played an important role in shaping our ideas about nekton, today no longer provides a sufficient basis for ecological and functional morphological investigations, since it affords no possibility of quantitatively assessing either the boundary between plankton and nekton or that between nekton and other ecomorphological types of biont. Thus Parin (1968), proceeding from Haeckel's principle, believes that in the epipelagic zone of the ocean the minimum size of nektonic fishes with a well-developed capacity for active swimming may be between 15 and 30 cm, as fishes shorter than 15 cm are unable to counter oceanic currents. Meanwhile young Leucaspius (Leucaspius delineatus) only 1.5 cm long, observed by this writer in ponds near Moscow proved capable of active horizontal migrations across the entire body of water, which, if Haeckel's definition is accepted, brings the border between planktonic and nektonic fish in this case to between 1.5 and 2.0 cm.